The effect of fertilization with some organic fertilizers of marine origin on the concentration of some nutrients elements mental on peach leaves and fruit variety May flower - ديب علي; هيفا سوسن; خربوتلي رشيد; دنده علاء (Latakia University Journal -Biological Sciences Series, 2020)
This research was carried out in Tartous Governorate on peach trees variety May flower aged 12 years at planting distances of 5X5 meter for studying the effect of fertilization with some organic fertilizers of marine origin on the concentration of some metal elements on the leaves and fruit of the variety May flower during the growth season of the year 2018 , with the use of Incosioid seaweed extract with the concentration of 0.50 mil/l , Marine with the concentration of 0.50 mil/l and Life green with the concentration of 4.5 g/l with sprinkling on the whole greenery in addition to soil with base soil fertilization . Here below are the most important results that we have got: - The effect of fertilization positively with the use of seaweed extract with its various concentrations in the content of the leaves and fruit of peach trees out of the major and minor metal elements compared with the control. - Common life treatment led to obvious increase in the content of leaves of N,P,K(2.38,0.33,1.79)% surpassing the other treatments including the control treatment. This also enhanced the content of the fruit of the above mentioned metal elements . - Common Anco treatment was distinguished for giving the best results in the content of leaves and fruit of Fe, Cu, Mn , Zn compared with the rest of treatments and the control treatment. -Common Marine treatment increased clearly the content of both leaves and fruit of Ca , Mg compared with the rest of studied treatments . This also was accompanied with the increase of the content of leaves and fruit of B .